2013
DOI: 10.1016/j.neuron.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of NPR-1 Reveals a Circuit Mechanism for Behavioral Quiescence in C. elegans

Abstract: SUMMARY Animals undergo periods of behavioral quiescence and arousal in response to environmental, circadian, or developmental cues. During larval molts, C. elegans undergoes a period of profound behavioral quiescence termed lethargus. Locomotion quiescence during lethargus was abolished in mutants lacking a neuropeptide receptor (NPR-1), and was reduced in mutants lacking NPR-1 ligands (FLP-18 and -21). Wild type strains are polymorphic for the npr-1 gene, and their lethargus behavior varies correspondingly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
180
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(193 citation statements)
references
References 52 publications
12
180
1
Order By: Relevance
“…The C. elegans homolog of the circadian clock protein Period is required for clocking larval development and thus the timing of lethargus-its messenger RNA (mRNA) levels track the molting cycle (Jeon et al 1999;Tennessen et al 2006;Monsalve et al 2011). Multiple additional conserved signaling pathways exhibit functional similarities in mammalian, insect, and nematode sleep, including epidermal growth factor signaling, protein kinase A (PKA) and G (PKG) activity, dopamine signaling, and pigment dispersing factor (PDF) signaling (Graves et al 2003;Kramer et al 2003;Snodgrass-Belt et al 2005;Van Buskirk and Sternberg 2007;Foltenyi et al 2007;Raizen et al 2008;Langmesser et al 2009;Choi et al 2013Choi et al , 2015Iwanir et al 2013;Singh et al 2014).…”
Section: Worm Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. elegans homolog of the circadian clock protein Period is required for clocking larval development and thus the timing of lethargus-its messenger RNA (mRNA) levels track the molting cycle (Jeon et al 1999;Tennessen et al 2006;Monsalve et al 2011). Multiple additional conserved signaling pathways exhibit functional similarities in mammalian, insect, and nematode sleep, including epidermal growth factor signaling, protein kinase A (PKA) and G (PKG) activity, dopamine signaling, and pigment dispersing factor (PDF) signaling (Graves et al 2003;Kramer et al 2003;Snodgrass-Belt et al 2005;Van Buskirk and Sternberg 2007;Foltenyi et al 2007;Raizen et al 2008;Langmesser et al 2009;Choi et al 2013Choi et al , 2015Iwanir et al 2013;Singh et al 2014).…”
Section: Worm Sleepmentioning
confidence: 99%
“…The nematode sleep circuitry includes multiple sensory circuits and classes of interneurons that display sleep-specific changes in activity and/or functional correlations (Schwarz et al 2011;Choi et al 2013Choi et al , 2015Iwanir et al 2013;Cho and Sternberg 2014). Glutamate and PDF neuropeptides both mediate excitatory outputs from sensory neurons to promote arousal (Choi et al 2013(Choi et al , 2015, consistent with pharmacological manipulations of glutamate in mammals (Juhász et al 1990;Alam and Mallick 2008;Li et al 2011) and the function of neuropeptides in vertebrates (orexin/hypocretin) and flies (PDF) (Sutcliffe and de Lecea 2002;Prober et al 2006;Parisky et al 2008;Choi et al 2015). As both molecular and circuit mechanisms can be conserved across phyla, C. elegans lethargus can provide insight into core functions and regulation of sleep (Nelson and Raizen 2013;Singh et al 2014).…”
Section: Worm Sleepmentioning
confidence: 99%
“…A combination of the neural connection diagram with molecular analyses will likely eventually lead to a systematic understanding of the neural regulation of a behavior, from key regulatory molecules to signaling integration in neural circuits. Several examples of such efforts include the dissection of a hub-and-spoke circuit that controls C. elegans social behavior ), the thermotaxis circuit (Kimata et al 2012), the circuit that generates long-lasting roaming and dwelling states , the mechanosensation circuit (Chalfie et al 1985), and the behavioral quiescence circuit (Choi et al 2013). We found that C. elegans strongly avoids MeSa, suggesting that this animal can be used for studying the molecular and neuronal mechanisms underlying the behavioral effects of MeSa.…”
mentioning
confidence: 99%
“…C. elegans is known for its easily manipulated genetics, small nervous system with mapped neuronal connectivity, stereotypical behaviors, and the ability to be studied efficiently in large numbers. Numerous studies have shown that C. elegans lethargus, a restful period that occurs before each molt of the cuticle during larval development, is neuronally regulated and likely orthologous to sleep in mammals (Van Buskirk and Sternberg 2007;Raizen et al 2008;Van Buskirk and Sternberg 2010;Choi et al 2013;Iwanir et al 2013;Turek et al 2013;Cho and Sternberg 2014;Singh et al 2014). Lethargus quiescence in C. elegans shares several characteristics with mammalian sleep: inactivity (decreased locomotion and cessation of pharyngeal pumping, or feeding), a specific posture, reduced response to aversive stimuli, and rapid reversibility (Cassada and Russell 1975;Raizen et al 2008;Schwarz et al 2012;Iwanir et al 2013;Cho and Sternberg 2014).…”
mentioning
confidence: 99%
“…Fascinatingly, molecules that regulate behavioral quiescence in C. elegans and Drosophila are conserved and influence sleep in mammals, indicating evolutionarily conserved origins of sleep and the potential utility of studying sleep in such simple animals Sehgal and Mignot 2011;. These molecules include the cAMP protein kinase A and cAMP response element-binding protein (CREB) signaling axis (Graves et al 2003;, cGMPdependent protein kinase Langmesser et al 2009), neuropeptides (van den Pol 2012Choi et al 2013;Nelson et al , 2014, dopamine (Singh et al 2014), transcription factor AP2 (Mani et al 2005;Turek et al 2013), and epidermal growth factor receptor (EGFR) (Snodgrass-Belt et al 2005;Van Buskirk and Sternberg 2007). Strikingly, EGFR has been shown to be required in only one neuron of C. elegans (the ALA interneuron) for proper induction of sleep-like quiescence behavior during lethargus and cellular stress-induced sleep-like quiescence (Van Buskirk and Sternberg 2007;Hill et al 2014).…”
mentioning
confidence: 99%